"Acceptance of social and labor market programs and regulations": Methodological report on the second survey - Gesine Stephan; Christopher Osiander; Monika Senghaas; Olaf Struck (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2021)
The FIS-funded project "Acceptance of social and labor market programs and regulations" asks citizens about their assessment of specific design alternatives for social and labor market policies in Germany. This report describes the design and the field organization of the second online survey conducted by the project. Furthermore, it presents a selectivity analysis of contact and participation probabilities as well as for consent to merge the survey data with administrative data. In the online survey described in this report, we use a factorial survey design. Furthermore, the survey asks a number of additional questions on demographic characteristics of participants as well as on their attitudes. Potential survey participants were drawn from the administrative data of the German Federal Employment Agency (FEA) and invited to participate in an online survey either by email or postal letter. – – Das FIS-geförderte Projekt "Die Akzeptanz sozial- und arbeitsmarktpolitischer Maßnahmen und Regelungen" befragt Bürgerinnen und Bürger zu ihrer Einschätzung konkreter Ausgestaltungsalternativen der Sozial- und Arbeitsmarktpolitik in Deutschland. Dieser Bericht beschreibt das Design und die Feldorganisation der zweiten Online-Befragung im Rahmen des Projekts. Er präsentiert zudem eine Selektivitätsanalyse der Kontakt- und Teilnahmewahrscheinlichkeiten sowie eine Analyse der Zustimmung zur Verknüpfung der Antworten mit prozessproduzierten Daten. Ein zentraler Bestandteil der hier beschriebenen Online-Befragung sind faktorielle Surveys. Darüber hinaus erhebt die Umfrage ausgewählte demografische Merkmale und Einstellungen der Teilnehmenden. Potenzielle Teilnehmende wurden aus den Prozessdaten der Bundesagentur für Arbeit (BA) gezogen und entweder per Email oder per Postanschreiben zur Teilnahme an der Befragung eingeladen.
Keywords: 330